The epigraphy from Liria: palaeographic review of some inscriptions (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this paper unpublished or not well known inscriptions from Liria (Valencia) are studied, as well as the published painted epigraphy is re-viewed.
Keywords: Iberian epigraphy; New inscriptions; Iberian palaeography